Analisis Capital Structure dalam Keuangan Islam - Muhammad Agus Salim; Ahmad Rodoni (JURNAL INDO-ISLAMIKA, 2017)
This paper studies the current development of the capital structure theory, to explore the connection between this theory and the Islamic finance, and to investigate the connection between the capital structure and the process of syari`ah (Islamic law) screening in three stock exchanges of syari`ah. Here, this article employs a qualitative approach by delving other scholars’ theories that have studied the capital structure of the Islamic finance. Next, this paper demontates an important finding; that is, limitation is necessary for the use of debt in a company that operates on the basis of Islamic principles. In this regard, as a debt has to have a favor for asset, the company, which operates on the basis of Islamic principles, is not to go beyond the real asset. The difference of the syari`ah screening model in those three stock exchanges is influenced by some crucial factors in the way the company decides its syari`ah screening model. They are, such as the difference of a social structure in a country, its modification of the monetary industry, and its variance of the school of thought adhered by some Muslim learned people.